2016
DOI: 10.1590/1518-8345.1431.2830
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological evaluation of the steam sterilization of assembled laparoscopic instruments

Abstract: Objective:assess the safety of steam sterilization of assembled laparoscopic instruments with challenge contamination. Method:a laboratory experimental study, using as test samples trocars and laparoscopic graspers. Geobacillus stearothermophillus ATCC-7953 was used, with a microbial population of 106UFC/Filter paper substrate, removed from the biological indicator. Three of them were introduced into each instrument at the time of assembly, and sterilized at pressurized saturated steam, 134oC for 5 minutes. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…While steam sterilization is a recommended method for sterilizing these instruments and has shown effectiveness, ethylene oxide treatment is also increasingly being used. [17][18][19][20] Despite the advantages of laparoscopic hysterectomy over invasive procedures, ensuring thorough sterilization of instruments before reuse is paramount. This case highlights the critical importance of adhering to proper sterilization protocols for laparoscopic instruments in hysterectomy procedures.…”
Section: Discussionmentioning
confidence: 99%
“…While steam sterilization is a recommended method for sterilizing these instruments and has shown effectiveness, ethylene oxide treatment is also increasingly being used. [17][18][19][20] Despite the advantages of laparoscopic hysterectomy over invasive procedures, ensuring thorough sterilization of instruments before reuse is paramount. This case highlights the critical importance of adhering to proper sterilization protocols for laparoscopic instruments in hysterectomy procedures.…”
Section: Discussionmentioning
confidence: 99%
“…One of the advised methods of sterilisation of laparoscopic instrument is steam sterilisation, which has showed good efficacy. 14 In recent days, laparoscopic instrument is subjected to ethylene oxide treatment for its sterilisation. 15 No doubt the laparoscopic hysterectomy has its advantages over the invasive hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the processing of articles through sterilization with the destruction of bacterial spores should be determined from the reading of the biological indicators that are used to monitor sterilization cycles. 20 The importance of reading the biological indicator after the incubation period related to its generation, identifying positivity or negativity of the microbial growth, since its technology is indispensable to guarantee security to the monitoring of the sterilization. 7,20 It was found in the results of this research with the multiprofessional team that only one (1%) participant reported that the biological indicator is used in the first sterilization cycle of the day and in all loads with implant materials, such as plaque and screws, and that the reading of the result is obtained in three hours, being verified the positivity or the negativity in the growth of microorganism.…”
Section: Englishmentioning
confidence: 99%